Smooth Running of English Written Test - Fathiah Izzati, Mohammad Fadzillah (UMPSA, 2022)
27 April 2022 - The Centre for Modern Languages(CML) jointly with the Student Affairs and Alumni Department (SAffAD) conducted an English Written Test for students who were shortlisted for UMP Foundation Excellence Scholarship Offer 2022.